2005
DOI: 10.1370/afm.345
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of Clinical Preventive Services in Family Medicine Offices

Abstract: BACKGROUND This study aimed to elucidate how clinical preventive services are delivered in family practices and how this information might inform improvement efforts. METHODSWe used a comparative case study design to observe clinical preventive service delivery in 18 purposefully selected Midwestern family medicine offi ces from 1997 to 1999. Medical records, observation of outpatient encounters, and patient exit cards were used to calculate practice-level rates of delivery of clinical preventive services. Fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
84
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(90 citation statements)
references
References 24 publications
6
84
0
Order By: Relevance
“…Such a focus might preempt preventive care, particularly more time-consuming preventive activities such as performing a Papanicolaou test or discussing CRC screening options or the pros and cons of PSA testing. 29,30 In addition, patients who value extended access may be more likely to seek out practices that offer it and to recognize (and report) that it is available, and such individuals may place a lower premium on prevention. While extended office hours have been associated with lower overall health care costs and fewer emergency department visits, 5,6 these findings underscore the need for further investigation of their impact on care outcomes, including preventive care.…”
Section: Discussionmentioning
confidence: 99%
“…Such a focus might preempt preventive care, particularly more time-consuming preventive activities such as performing a Papanicolaou test or discussing CRC screening options or the pros and cons of PSA testing. 29,30 In addition, patients who value extended access may be more likely to seek out practices that offer it and to recognize (and report) that it is available, and such individuals may place a lower premium on prevention. While extended office hours have been associated with lower overall health care costs and fewer emergency department visits, 5,6 these findings underscore the need for further investigation of their impact on care outcomes, including preventive care.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 The face-to-face clinical encounter of the PHE seems to be a commonly used strategy. Crabtree et al 21 noted that the clinical encounter with the physician or allied health clinician was the primary locus for delivering preventive services. Although several of the primary care practices included in their study had nursing and/or front office staff involved by sending reminders or having patients complete intake forms, it was up to clinicians to follow through in the examination room.…”
Section: How Best To Insure Screening?mentioning
confidence: 99%
“…19 This analysis examines how small, independent primary care practices without a formal quality improvement program can implement change management using a team approach with 2 coleaders, each in a different professional role, to institute changes in primary care settings. Compared with many interventions that rely on outside facilitators, 18,20,21 this study demonstrated the feasibility of using a modified improvement collaborative model to train and support practice staff in basic change management strategies 22 ; a follow-up report has confirmed that most practices were continuing to use depression care improvements 3 years after the beginning of the intervention. 23 This analysis enhances our understanding of how the 2 coleaders collaborated and contributed to these results and suggests an approach that can be adapted to independent practice settings.…”
mentioning
confidence: 73%